2016
DOI: 10.1155/2016/2061248
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Status of SP1 Sites within miR-23a-27a-24-2 Promoter Region Influences Laryngeal Cancer Cell Proliferation and Apoptosis

Abstract: DNA methylation plays critical roles in regulation of microRNA expression and function. miR-23a-27a-24-2 cluster has various functions and aberrant expression of the cluster is a common event in many cancers. However, whether DNA methylation influences the cluster expression and function is not reported. Here we found a CG-rich region spanning two SP1 sites in the cluster promoter region. The SP1 sites in the cluster were demethylated and methylated in Hep2 cells and HEK293 cells, respectively. Meanwhile, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…In a study conducted in China, showed that mir-23a in Serum has a potential biomarker for recognition of type 2 diabete. [17][18][19][20][21][22] An exonic mir-155 with rs767649 (T/A) polymorphism in the upstream region of the pre-mir-155 gene is transcribed from the B-cell integration cluster (BIC). It has been suggested that mir155 modulate host antiviral immune response by elevating type I IFN signaling, and contribute in diverse biological processes such as immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in China, showed that mir-23a in Serum has a potential biomarker for recognition of type 2 diabete. [17][18][19][20][21][22] An exonic mir-155 with rs767649 (T/A) polymorphism in the upstream region of the pre-mir-155 gene is transcribed from the B-cell integration cluster (BIC). It has been suggested that mir155 modulate host antiviral immune response by elevating type I IFN signaling, and contribute in diverse biological processes such as immunity.…”
Section: Discussionmentioning
confidence: 99%
“…miR 24: its upregulation, similar to miR27a, leads to promotion of proliferation and early apoptosis inhibition in LSCC 18 ; according to Xu et al, miR24 expression is significantly lower in LSCC cell lines and it inhibits growth-related apoptosis and enhances radiosensitivity in LSCC 36 .…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether reported methylation of the miR-23a~27a~24-2 cluster promoter [21] accounts for the transcriptional change after radiation, methylation was blocked 3 h prior to (Fig. 2B).…”
Section: 2radiation-induced Methylation Leads To Reduced Pri-mir-2mentioning
confidence: 99%
“…Evidence for a link between transcriptional repression and methylation of the cluster promoter comes from the study of Wang and Zhang et al [21]. These authors showed that demethylated SP1 sites in GC-rich regions of the cluster promoter result in over-expression of hsa-miR-23a~27a~24-2 in laryngeal cancer cells.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation